Desain Pembelajaran Pendidikan Agama Islam (PAI) dengan Pendekatan Deep Learning di SMA - Abdussyukur; Zulfah, Hefty (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This study aims to formulate a conceptual design for Islamic Religious Education (PAI) learning in senior high schools based on the Deep Learning (DL) approach. The research employs a qualitative approach, utilising library research and conceptual analysis methods. The primary source of this study is the academic manuscript